A note on the top Lyapunov exponent of linear cooperative systems - Benaim, Michel; Claude Lobry; Tewfik Sari; Strickler, Edouard (My University, 2023)
In a recent paper [Asymptotic of the largest Floquet multiplier for cooperative matrices Annales de la Facult\'e des Sciences de Toulouse, Tome XXXI, no 4 (2022)] P. Carmona gives an asymptotic formulae for the top Lyapunov exponent of a linear T-periodic cooperative differential equation, in the limit T goes to infinity. This short note discusses and extends this result.
Keywords: math.DS; math.PR; 60J25, 37H15, 34A30